Challenges Facing National Park Management: A Case Study of Kainji Lake National Park, Nigeria - J. O. Onihunwa; O. A. Akande; E. A. Irunokhai; N. Mohammed; A. S. Wealth (Journal of Applied Sciences and Environmental Management, 2023)
Generally, the problems associated with national park management in Nigeria include loss of wildlife habitats, poaching, overhunting, and illegal logging and grazing. Hence, the objective of this study is to evaluate the numerous challenges facing National Park Management in Nigeria using the Kainji Lake National Park as a case study using personal interview and administration of structural questionnaire to select one hundred and ninety four (194) respondents from the total population and data obtained was analyzed using descriptive statistics. The result of demographic characteristics of respondents sampled indicates that the male respondents were dominant (75.7%) and majority of the 51.4% of the sampled populations’ falls between age group 35-44 years. The finding further revealed that majority of the respondents was married (71.0%). 59.8% of the respondents had tertiary education while 40.2% had secondary education. Also, majority of the respondents are Muslims (71.0%) while 29.0 are Christian. Majority of the respondents (52.3%) had worked between 11-20 years while ≥21 are the least with 17.8%. The major challenges confronting Kainji Lake National Park as identified by the park staffs are insufficient fund and lack/shortage of manpower.The effects of these challenges on Wildlife management are reduction in management practices, makes work difficult and reduction in wildlife population. The measures taken in managing the identified challenges in the study area are provision of incentives/bonus to the staff, adequate funding, provision of modern equipment and facilities etc. The study therefore concludes that for effective conservation of biodiversity to be achieved in this premier national park of Nigeria, the identified challenges must be addressed.